PENGELOLAAN BENDA SITAAN DAN RAMPASAN NEGARA PADA RUMAH PENYIMPANAN BENDA SITAAN NEGARA (RUPBASAN) KLAS 1 BANDAR LAMPUNG - Neta, Yulia (Fakultas Hukum Universitas Lampung, 2012)
The research studied about the arrangement of confiscated goods and countryâs sweeping at Rupbasan klas 1 in Bandar Lampung. The research used normative empirical approach. The result of research indicated that the rule of the arrangement of countyâs confiscated and sweeping goods started from the acception at Rupbansan, then it was noted in registration book, then, it was done a research such as to investigate, examine, and estimate the goods by a researcher. Finally, it was done storage and maintenance.